Chapter 8 – Hands wet: counting the fish - Santos, Jorge (Septentrio Educational, 2015)
QUESTIONS ASKED How do biologists count organisms in the field? How do they design their sampling? How can one scale or extrapolate observations to other areas? Sampling design scaling Direct counting (general)